P-037 A fluorescent probe for Reactive Oxygen Species (ROS) detection identifies spermatozoa with a better reporductive performance. (30th June 2022) - Baldi, E; Traini, G; Tamburrino, L; Bini, F; Raffaelli, G; Vignozzi, L; Marchiani, S
Abstract: Study question: Could Reactive Oxygen Species (ROS) detected in human spermatozoa represent a predictive marker of fertilization ability? Summary answer: ROS detected by CellROX® Orange probe is related to a better sperm quality and function, indicating the sensitivity of the probe to identify physiological ROS. What is known already: Oxidative stress (OS), defined as an unbalance between ROS production and antioxidant defenses, is one of the causes of male infertility. A small amount of ROS is necessary for the physiological sperm function, however high ROS levels could impair fertility potential inducing damages at membrane, protein and DNA levels. Previous studies performed by using different methods and probes for OS evaluation in semen or in spermatozoa highlighted the negative role of ROS on sperm functions. However, such studies were not conclusive because of the small number of included subjects and of high variability in the cohorts. Study design, size, duration: Observational study conducted on 73 male partners of infertile couples attended consecutively to the Andrology Laboratory of Careggi University Hospital of Florence from September to December 2021. Analyses were performed on both washed and Swim-up selected spermatozoa. Participants/materials, setting, methods: After routine semen analysis, washed and Swim-up selected spermatozoa were incubated with CellRox®Orange (a fluorescent probe able to reveal OS in viable cells), at the concentration of 1 µM for 30 minutes at 37°C, 5%CO2, and revealed by flow cytometry. Sperm DNA fragmentation (by TUNEL/PI method), sperm kinematic parameters and hyperactivated motility (by C.A.S.A. system) were also assessed. In some samples a double staining with CellRox®Orange and Annexin V (which stains phosphatidylserine externalization) was performed. Main results and the role of chance: We found that the percentage of spermatozoa positive to CellRox® Orange is positively correlated with routine seminal parameters. Although this result appears in contrast with most studies in literature reporting negative correlations between OS and semen parameters, it can be explained by the fact that the probe is specific for viable spermatozoa characterized by a better motility and morphology. Considering the importance of distinguishing between positive and negative ROS in spermatozoa, we further investigated the significance of ROS detected by this probe. To understand whether the probe marks spermatozoa with a better quality, CellRox® Orange positivity was evaluated in Swim-up selected spermatozoa finding significantly higher levels of CellRox® Orange positivity respect to unselected samples. Furthermore, the fact that most of the CellRox® Orange positive spermatozoa were negative for Annexin V (which reveals cells with early signs of apoptosis) is a further confirmation of the good quality of CellRox® Orange positive spermatozoa. Another evidence is represented by the finding that we observed a negative correlation between OS detected by CellRox® Orange and sperm DNA fragmentation, although several studies have shown a positive relationship between these two parameters (when OS is measured by different probes). Limitations, reasons for caution: Up to now, the study involved a limited number of subjects. Further experiments should be performed to increase the number of subjects in order to confirm the results. Wider implications of the findings: Results of this study together with those previously published evidence that different OS is detected depending on which probe is used. CellRox® Orange seems to be sensible for physiological ROS detection, therefore, it could be employed in future studies aimed to evaluate the association between OS and assisted reproduction outcomes. Trial registration number: not applicable